2003
DOI: 10.1089/108729103771928717
|View full text |Cite
|
Sign up to set email alerts
|

Symptoms of Posttraumatic Stress and Death Anxiety in Persons with HIV and Medication Adherence Difficulties

Abstract: The present study examined the frequency and correlates of self-reported symptoms of posttraumatic stress among patients with HIV and medication adherence problems. Self-report data revealed that more than half of participants met diagnostic criteria for posttraumatic stress disorder (PTSD) according to the Posttraumatic Diagnostic Scale PDS. Death anxiety was associated with overall PTSD symptom severity scores as well as severity scores for reexperiencing, avoidance, and arousal symptoms. The association bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
89
1
6

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(106 citation statements)
references
References 56 publications
10
89
1
6
Order By: Relevance
“…According to results, the first hypothesis was supported. Death anxiety predicted PTSD as supported by previous research [16][17][18]. The relationship between death anxiety and PTSD is confirmed and provides an interesting opportunity to suggest the pathway.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…According to results, the first hypothesis was supported. Death anxiety predicted PTSD as supported by previous research [16][17][18]. The relationship between death anxiety and PTSD is confirmed and provides an interesting opportunity to suggest the pathway.…”
Section: Discussionsupporting
confidence: 78%
“…Martz found that death anxiety predicted the severity of PTSD symptoms among people with spinal cord injury [16]. Other studies found that death anxiety predicted both overall PTSD severity as well as the severity for the three main clusters of PTSD symptoms (reexperiencing, avoidance and hyperarousal) among patients with HIV [17,18]. Given the paucity of studies which examined the contribution Death Anxiety Resilience 4 of death anxiety to PTSD, more research is needed to replicate and clarify this relationship.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that medication adherence to HAART therapy is decreased in HIV patients with comorbid PTSD and depression. 30,31 A recent study by Lockwood et al demonstrated that adherence with antidepressant medication was poor among PTSD patients discharged from a residential treatment program during long term follow-up. 32 In addition, prior reports have found an increased likelihood of missed appointments, underuse of medications, abuse of prescription psychoactive agents, and the propensity of self-adjust medical treatments among patients with PTSD.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15] Moreover, recent research has found high levels of self-reported posttraumatic stress disorder (PTSD) symptomatology among HIV-positive individuals after their initial diagnosis. 16,17 Given that HIV-positive individuals may be experiencing a wide variety of stressors, it is of interest to examine the impact of various aspects of stress on treatment adherence. Whereas some researchers have focused on the cumulative impact of self-reported acute stressful life events on outcomes such as depressive symptomatology, others have focused on the role of one's perception of stress.…”
Section: Introduction Tmentioning
confidence: 99%